2015
DOI: 10.1007/s40139-015-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase Type 5 as a Candidate Therapeutic Target in Cancers

Abstract: The global burden of cancer is largely increasing because of population aging and growth alongside an adoption of cancer-causing lifestyle choices. The majority of cancers can be treated, and certain can be cured, depending on their type, location, and stage. Although conventional therapies have changed the natural history of the disease, many tumors exhibit drug resistance and severe adverse effects remain major therapeutic hurdles. On the other hand, clinical trials and meta-analyses have demonstrated that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…An increasing amount of studies have been reported to date on the association between PDE5 expression and cancer, most of which identify increased expression levels of PDE5 in a consistent number of human cancers compared to normal or surrounding non-neoplastic tissues. In addition, according to recent findings, PDE5i has been shown to act as potential anti-cancer drugs on tumor cell lines, either for their chemosensitizing effects or as chemopreventive agents (Barone et al, 2015). Nevertheless, the majority of the reports rely on preclinical evidences making it difficult to draw clear conclusions and to provide appropriate clinical guidelines relating thereto (Barone et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing amount of studies have been reported to date on the association between PDE5 expression and cancer, most of which identify increased expression levels of PDE5 in a consistent number of human cancers compared to normal or surrounding non-neoplastic tissues. In addition, according to recent findings, PDE5i has been shown to act as potential anti-cancer drugs on tumor cell lines, either for their chemosensitizing effects or as chemopreventive agents (Barone et al, 2015). Nevertheless, the majority of the reports rely on preclinical evidences making it difficult to draw clear conclusions and to provide appropriate clinical guidelines relating thereto (Barone et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…), thus regulating a countless number of biological processes, including cell growth and adhesion, energy homeostasis, neuronal signaling, and smooth muscle relaxation (Lin et al, 2000;Soderling & Beavo, 2000;Murthy, 2001;Dolci et al, 2006). Expression of PDE5 and the cGMP-signaling pathway turns out to be often altered in several human cancers, such as colon, breast, lung, and bladder carcinomas (Barone et al, 2015). However, the effective role of cGMP in tumorigenesis is still debated and, above all, it is heavily dependent upon the tumor type and the model system investigated (Barone et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The cGMP signaling plays an important role in cell proliferation, differentiation, angiogenesis, apoptosis, and tumor-logical activity [18] . The mRNAs of specific-cGMP PDEs such as PDE5 have been shown to be increased in various cancers; thus, the inhibitors of this enzyme could be suitable therapeutic candidates for breast cancer [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that PDE5 and cGMP signaling pathways can be considered as new candidates for discovering novel therapeutic strategies toward treating breast cancer , especially triplenegative subtype [12,18,19] . Nevertheless, common inhibitors of PDE5 have been reported to possess a well-established side effect in clinical experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The effects are due to the dilation of arterial vessels, as well as non-selective inhibition of PDE1 which also hydrolyzes cGMP and is located predominantly in vascular smooth muscle cells [19,22]. In addition, PDE5 inhibitors are not only correlated with erectile dysfunction therapy; for example, tadalafil has recently been approved for the treatment of benign prostatic hyperplasia, pulmonary hypertension and lower urinary tract symptoms [22][23][24], and recent studies have pointed to PDE5 inhibitors as a new strategy for the treatment of certain types of tumors [25], demonstrating the importance of these compounds [26]. Researchers have investigated the correlation of important residues in PDE5 with the selectivity of these ligands [27], which directly impacts the therapeutic applications of the aforementioned drugs.…”
mentioning
confidence: 99%